ExoMol line lists – XLV. Rovibronic molecular line lists of calcium monohydride (CaH) and magnesium monohydride (MgH). Issue 4 (11th February 2022) - Owens, Alec; Dooley, Sophie; McLaughlin, Luke; Tan, Brandon; Zhang, Guanming; Yurchenko, Sergei N; Tennyson, Jonathan
ABSTRACT: New molecular line lists for calcium monohydride ( 40 Ca 1 H) and magnesium monohydride ( 24 Mg 1 H) and its minor isotopologues ( 25 Mg 1 H and 26 Mg 1 H) are presented. The rotation-vibration-electronic (rovibronic) line lists, named XAB, consider transitions involving the X ^2Σ ^+, A ^2Π, and B/B^′ ^2Σ ^+ electronic states in the 0–30 000 cm −1 region (wavelengths λ > 0.33 μm) and are suitable for temperatures up to 5000 K. A comprehensive analysis of the published spectroscopic literature on CaH and MgH is used to obtain new extensive data sets of accurate rovibronic energy levels with measurement uncertainties and consistent quantum number labelling. These data sets are used to produce new spectroscopic models for CaH and MgH, composed of newly empirically refined potential energy curves and couplings in/between the different electronic states (e.g. spin-orbit, electronic angular momentum, Born-Oppenheimer breakdown, spin-rotation, Λ-doubling), and previously published ab initio transition dipole moment curves. Along with Einstein A coefficients, state lifetimes and Landé g -factors are provided, the latter being particularly useful as CaH and MgH can be used to probe stellar magnetic fields. Computed energy levels have been replaced with the more accurate empirical values (if available) when post-processing the line lists, thus tailoring the line lists to high-resolution applications. The XAB line lists are available from the ExoMol database at www.exomol.com and the CDS astronomical database.